2023
DOI: 10.1038/s41467-023-36569-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of HIV-1 maturation inhibitor binding and activity

Abstract: HIV-1 maturation inhibitors (MIs), Bevirimat (BVM) and its analogs interfere with the catalytic cleavage of spacer peptide 1 (SP1) from the capsid protein C-terminal domain (CACTD), by binding to and stabilizing the CACTD-SP1 region. MIs are under development as alternative drugs to augment current antiretroviral therapies. Although promising, their mechanism of action and associated virus resistance pathways remain poorly understood at the molecular, biochemical, and structural levels. We report atomic-resolu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…These observations collectively point to an induction of asymmetry within the binding pocket (Figures and ). The binding of 3 to the 6-HB reduced the dynamic mobility of IP 6 and the side chains of residues within SP-1, and the MI did not appear to rotate freely within the binding pocket, an observation that contrasted with the results of a detailed molecular dynamics study. , Further experimentation indicated that the binding of 3 to the Ala 364 Val-resistant virus was attenuated, while the Val 370 Ala mutation reduced the conformational stability of SP-1, presumably allowing for a more facile transition to the conformation that exposes the cleavage site to HIV-1 protease. ,, The deduced binding pose suggests that MIs like 1 and 2 , which introduce larger substituents at C-17 of the core, extend interactions of the molecule with elements of SP-1, including projecting into the region defined by the QVT motif, thereby reducing the mobility of the 6-HB complex in a fashion that prevents access to the conformation recognized by the protease. ,, Some of the mutations that confer resistance to MIs, notably Val 370 , are involved in interstrand interactions that presumably destabilize the 6-HB complex and enhance conformational dynamics, which promotes cleavage site exposure. Collectively, these observations are consistent with the binding dissociation data developed for 1 and 2 in virus-like particles (VLPs) expressing WT and mutated sequences that are compiled in Table .…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…These observations collectively point to an induction of asymmetry within the binding pocket (Figures and ). The binding of 3 to the 6-HB reduced the dynamic mobility of IP 6 and the side chains of residues within SP-1, and the MI did not appear to rotate freely within the binding pocket, an observation that contrasted with the results of a detailed molecular dynamics study. , Further experimentation indicated that the binding of 3 to the Ala 364 Val-resistant virus was attenuated, while the Val 370 Ala mutation reduced the conformational stability of SP-1, presumably allowing for a more facile transition to the conformation that exposes the cleavage site to HIV-1 protease. ,, The deduced binding pose suggests that MIs like 1 and 2 , which introduce larger substituents at C-17 of the core, extend interactions of the molecule with elements of SP-1, including projecting into the region defined by the QVT motif, thereby reducing the mobility of the 6-HB complex in a fashion that prevents access to the conformation recognized by the protease. ,, Some of the mutations that confer resistance to MIs, notably Val 370 , are involved in interstrand interactions that presumably destabilize the 6-HB complex and enhance conformational dynamics, which promotes cleavage site exposure. Collectively, these observations are consistent with the binding dissociation data developed for 1 and 2 in virus-like particles (VLPs) expressing WT and mutated sequences that are compiled in Table .…”
mentioning
confidence: 96%
“…Virions produced in the presence of 3 were non-infectious and exhibited a morphology in which the capsid core of the virion adopted a spherical disposition rather than the classic cone shape that is associated with correctly functioning HIV-1 particles. However, 3 was not a direct inhibitor of HIV-1 protease, pointing to a unique mechanism that began to be more fully understood at the molecular level from structural studies conducted long after the compound had entered clinical trials and which continue to provide critical insights. In clinical study, 3 had demonstrated an effective reduction in viral load in HIV-1-infected individuals susceptible to the drug; however, approximately 50% of the patients failed to experience a decline in viremia . The dichotomous response was traced to the presence of baseline polymorphisms in the Gag protein in a subset of the patient population that represented a source of inherent resistance and which meant that patients would need to be pre-screened for susceptibility prior to being prescribed the drug. This ultimately led to the compound being abandoned by its sponsors on June 8, 2010. , …”
mentioning
confidence: 99%
See 3 more Smart Citations